If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x = -2x + 44 Reorder the terms: 9x = 44 + -2x Solving 9x = 44 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 9x + 2x = 44 + -2x + 2x Combine like terms: 9x + 2x = 11x 11x = 44 + -2x + 2x Combine like terms: -2x + 2x = 0 11x = 44 + 0 11x = 44 Divide each side by '11'. x = 4 Simplifying x = 4
| 8x-4[5-3(x+1)]=0 | | 4(2n+1)-5n=5 | | 2x+6x-2=-34 | | 4x-7=-1-8x | | 15-n=3n | | x+30=12x-14 | | x+3x=1083 | | 6[2-(5+4x)]-2=-20+2(1-13x) | | 0=4.9x^2+12x-80 | | Y^2-5y+8=0 | | =-6a(-5)(2b) | | 73x+63=20x | | 5(-7-6x)=-55 | | 4x-5(2x+60)=158 | | 4(2x+7)=2(x-14)-2 | | t=082t | | 0.05-0.002x=0.75+0.198x | | 12n^2+7n-10=0 | | 8(7-6n)=-1-48n | | -12=4*b | | -t/4=20.5 | | 5x+2=4y+2 | | -6y=7.8 | | -3(d-5)=2(4s-9) | | (5-u)(4u+3)=0 | | 4x^2+11x=63 | | 5(cot^2)x=4 | | 7v-5(v+1)=3v-5(1-v) | | m(-7)=24 | | (5-y)(4u+3)=0 | | 2x+112=2x+156 | | 7p+(7-p)-(p+22)=0 |